Answer:
The solution of the equation is 15
Explanation:
* Lets explain how to solve the problem
- The equation is 3(2x + 5) = 3x + 4x
- The solution of the equation is the value of x
Lets find the value of x
- The left hand side is 3(2x + 5) lets simplify it
- Multiply the two terms of the bracket by 3
∵ 3(2x+ 5) = 3 × 2x + 3 × 5
∴ 3(2x + 5) = 6x + 15
- The right hand side is 3x + 4x
∵ They are like terms, then we will add them
∴ 3x + 4x = 7x
- Now equate the left hand side and the right hand side
∴ 6x + 15 = 7x
- Subtract 6x from the two sides
∴ 15 = 7x - 6x
∴ x = 15
∵ x is the solution of the equation
∴ The solution of the equation is 15